Poor sleep and high anxiety levels in women with functional hypothalamic amenorrhoea: A wake-up call for physicians? - Anastasios Tranoulis; Dimitra Georgiou; Alexandra Soldatou; Varvara Triantafyllidi; Dimitios Loutradis; Lina Michala (Elsevier, 2019)
Objective: To assess sleep disorders (SleD) in women with functional hypothalamic amenorrhoea (FHA) and to identify possible associations with known FHA predisposing factors. Study design: We conducted a prospective case-control study spanning the period January 2016 to April 2018. We recruited forty-one FHA women and 86 healthy controls. We assessed SleD and other FHA predisposing factors via self-reported questionnaires. The Spearman's correlation coefficient (rho) was used to examine possible correlations among the different variables. Multivariate logistic regression analysis was conducted to identify independent factors associated with SleD. Results: Women with FHA reported having higher SleD (p = 0.004), abnormal eating attitudes (p < 0.0001), higher anxiety levels (AL) (p < 0.0001), overweight preoccupation (P < 0.0001) and increased weekly physical activity (p = 0.004). There was a significant positive correlation between SleD and AL (rho = 0.88, p < 0.0001). Significant correlation was also found between AL and several Athens insomnia scale constituents, including sleep induction (rho = 0.53, p = 0.0004), awakenings during the night (rho = 0.6, p < 0.0001), final awakening (rho = 0.42, p = 0.006), total sleep duration (rho = 0.64, p < 0.0001), quality of sleep (rho = 0.63, p < 0.0001), well-being during the day (rho = 0.34, p = 0.03) and sleepiness during the day (rho = 0.51, p = 0.007). High AL were correlated with 2.83-fold increased SleD risk (p = 0.04). Conclusion: FHA women are seemingly more prone to SleD and those with SleD suffer from higher AL. In view of this evidence, the potential rationale of adding psychological and SleD evaluation to their clinical care is highlighted. Keywords: Functional hypothalamic amenorrhoea, Anxiety, Sleep disorders